Optimizing Sustainable Tourism in North Sumatra: An Analytic Hierarchy Process Approach Using Alternative Sustainability Metrics - Sinulingga, Samerdanta; Pohan, Riko Andika Rahmat; Januarini, Erna (Journal of Research in Mathematics Trends and Technology, 2024)
Sustainable tourism focuses on minimizing negative impacts on the environment and local communities while maximizing economic benefits. This study identifies sustainable tourist destinations in North Sumatra using the Analytic Hierarchy Process (AHP) with various sustainability criteria. Beyond common criteria (environmental, economic, and social), it includes alternative metrics like carbon footprint, biodiversity, energy consumption, water management, community participation, local economic revenue, air quality, and visitor satisfaction. Hypothetical scores for 15 destinations were analyzed, and criteria weights were set based on sustainability priorities. Simulations considering budget constraints optimized destination selection. Results indicated that Pulau Samosir, Air Terjun Sipiso-Piso, and Taman Alam Lumbini scored highest in sustainability. These were selected for their top performance against sustainability criteria. The study concludes that incorporating alternative sustainability metrics provides a comprehensive perspective, making the model a valuable tool for policymakers and tourism managers. It also demonstrates that significant sustainability can be achieved even within budget constraints.